India Shoots for the Moon. - Seema Singh
The Indian space program has attained a certain maturity after several decades of steady effort. It includes the launch of a four-stage rocket to put satellites into low-Earth orbit for Indonesia and Argentina scheduled by the end of December 2006 or early January 2007. The program is also scheduled to test launch a more powerful, three-stage rocket, designed to put much larger satellites into geosynchronous orbits in January and a lunar probe in 2007. All these activities have helped bring more international credibility and acceptance to India's space program
Keywords: Indian space program; Four-stage rocket; Geosynchronous orbits; Low-Earth orbit; Lunar probe